2015
DOI: 10.3906/kim-1502-55
|View full text |Cite
|
Sign up to set email alerts
|

Kojic acid in organic synthesis

Abstract: The reactions of kojic acid in organic synthesis are reviewed. The aim of this review is to cover the literature up to the end of 2014, showing the distribution of publications involving kojic acid chemistry in the synthesis of various pyrone containing compounds, pyridine and pyridone heterocycles, and also other organic compounds. First, introductory text about the preparation, biological, and industrial applications, and the chemical properties of kojic acid is given.Then its uses in organic synthesis are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 129 publications
(150 reference statements)
0
20
0
Order By: Relevance
“…For further optimization of reaction conditions, we tested acetonitrile, water and ethanol/water mixtures as solvents ( Table 1, entries [14][15][16][17], and found that the desired product was obtained at a higher yield in C 2 H 5 OH 95 % ( Table 1, entry 17). In addition, in view of the benefits of solvent-free conditions, we attempted to perform the model reaction under these conditions, but found that the reaction mixture was solidified, and the results showed that the reaction under these conditions was not efficient (Table 1, entries 18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For further optimization of reaction conditions, we tested acetonitrile, water and ethanol/water mixtures as solvents ( Table 1, entries [14][15][16][17], and found that the desired product was obtained at a higher yield in C 2 H 5 OH 95 % ( Table 1, entry 17). In addition, in view of the benefits of solvent-free conditions, we attempted to perform the model reaction under these conditions, but found that the reaction mixture was solidified, and the results showed that the reaction under these conditions was not efficient (Table 1, entries 18).…”
Section: Resultsmentioning
confidence: 99%
“…Because of the phenol-like properties of kojic acid, most of its MCRs involve the enolic moiety of this compound [16]. Threecomponent reaction of kojic acid, aldehyde and 1,3-dione has been achieved to afford dihydropyrano [3,2-b]chromenedione derivatives [17].…”
Section: Introductionmentioning
confidence: 99%
“…In continuing our research on nanocatalysts [10,11,40,41] and heterocyclic chemistry [42][43][44] To a preheated mixture of FeCl 3 6H 2 O (4.8 mmol, 1.3 g) and FeCl 2 4H 2 O (2.4 mmol, 0.48 g) in 20 mL of DI water at 40 C, glycine (6.1 mmol, 0.46 g) was added and the pH was adjusted to 11 using ammonia solution, and it was re uxed for 6 h under N 2 ow. By separation of the obtained precipitate using an external magnetic eld and then washing with DI water, and drying in oven at 60 C for 3 h, glycine capped Fe 3 O 4 magnetic nanoparticles were obtained.…”
Section: Introductionmentioning
confidence: 98%
“…[40] Kojic acid and its derivatives are an important class of pyranannulated heterocycles which can be found in natural and synthetic compounds. [41,42] Therefore, the development of novel methods for the efficient and convenient SCHEME synthesis of libraries of these compounds is an important field for modern medicinal and combinatorial chemists.…”
Section: Introductionmentioning
confidence: 99%